LEGAL CERTAINTY FOR HEALTH FACILITIES IN PROVIDING REFERRAL LETTER ON PATIENT REQUESTS IN THE JKN ERA (JURIDICAL REVIEW OF THE SJSN LAW AND BPJS HEALTH LAW) - Satria, Beni (RADJA PUBLIKA, 2022)
The main problem in this research is a policy problem, namely the problem of legal policy in regulating the rules of legal certainty for health facilities. Therefore the approach to this problem is a policy-oriented approach. However, considering that the main target of this research is legislative policy in formulating legal certainty for health facilities in carrying out their duties and functions, the approach is mainly taken with a juridical-normative approach. This research was conducted at the Blangkejeren Public Health Center, Lhoksukon City, Central Aceh, with literature studies at the Panca Budi University Library and internet searches. The data sources of a research are primary data and secondary data. Because this research is a normative legal research, the sources studied are secondary data sources. Legal certainty of payment for health services has provided legal certainty to Health Service Providers (PPK) as regulated in Presidential Regulation Number 19 of 2016 concerning the Second Amendment to Presidential Regulation Number 12 of 2013 concerning National Health Insurance (JKN). However, this change still does not provide legal certainty for BPJS patients when problems occur related to the amount of payments that must be paid by BPJS to Health Service Providers, if there are patients who experience/require to be treated with costs that exceed the rates determined by BPJS. Legal consequences if there is no legal certainty for health services